2018
DOI: 10.1590/1413-70542018423031117
|View full text |Cite
|
Sign up to set email alerts
|

Silvopastoral systems drive the nitrogen-cycling bacterial community in soil

Abstract: Intercropping tree legumes with forage grasses in a silvopastoral system can avoid pasture degradation benefiting the soil. In such a system, nitrogen (N) is supplied by symbiosis between legumes and bacteria. However, the pasture quality determines the action of free-living nitrogen-fixing bacteria, which possess nifH genes, which encode nitrogenase enzyme. Ammonium-oxidizing bacteria (AOB), involved in the nitrification step, can be evaluated by specific regions of the 16S rRNA corresponding to AOB. Thus, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
1
17
0
4
Order By: Relevance
“…Both silvopastoral systems had significant increases in soil total N content, likely due to biological N fixation in symbiosis with rhizobia, as also seen by Marini, Guimarães, Dartora, Lana, and Pinto Júnior (2015). Barros et al (2018) have shown that, with this experiment at 0 and 4 m away from legume row, the diazotrophic and total bacteria communities were similar and more abundant than under single signalgrass.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Both silvopastoral systems had significant increases in soil total N content, likely due to biological N fixation in symbiosis with rhizobia, as also seen by Marini, Guimarães, Dartora, Lana, and Pinto Júnior (2015). Barros et al (2018) have shown that, with this experiment at 0 and 4 m away from legume row, the diazotrophic and total bacteria communities were similar and more abundant than under single signalgrass.…”
Section: Discussionmentioning
confidence: 54%
“…In northeastern Brazil, one such system of intercropping signalgrass (Brachiaria decumbens) with shrub-tree legumes (gliricidia [Gliricidia sepium] and sabia [Mimosa caesalpiniaefolia]) has shown significant amounts of biological N fixation (Apolinário et al, 2016). Barros et al (2018) have also shown this same system type benefits the diazotrophic microbial community.…”
mentioning
confidence: 99%
“…GABY & BUCKLEY (2017) used the nifH gene in PCR quantitative (qPCR), finding good representability among their samples; although, our non-quantitative amplification reaction has also been well elaborating. Recently, some studies in tropical and dry lands environments related the contribution of organic nutrients with the energy required to nifH genes express activity (BARROS et al, 2018;PEREG et al, 2018). However, we emphasized that in our research all litter inputs are withdrawn by local farmers and; therefore, only residues from the roots systems of castor bean and maize are contributing with the energy necessary for the nifH gene activity on these soils.…”
Section: Resultsmentioning
confidence: 87%
“…Segundo Barros et al, (2018), a produção forrageira pode ser afetada pelo dossel sombreado dos sistemas silvipastoris ao longo do ano, especialmente em climas subtropicais e temperados. Isso pode afetar as características das plantas forrageiras fazendo com que as pastagens sombreadas não apresentem produtividades em níveis equivalentes às das pastagens sem sombra.…”
Section: Resultados Eunclassified
“…Ao estudarem o Kikuyu (Pennisetum clandestinum) planta com alto potencial de integração de carbono, Barros et al (2018) observaram que as raízes (20 cm), as hastes mortas e as folhas foram os compartimentos com os maiores estoques de carbono em sistemas silvipastoris com valores 4,52, 3,58 e 1,9 Mg C ha -1 ano -1 , respectivamente. Foi observado que biomassa total de raízes finas e grossas, desempenha um papel relevante na redução de GEE, na conservação de solos tropicais, na ciclagem de nutrientes, e consequentemente na massa do dossel forrageiro e carbono.…”
Section: Resultados Eunclassified